Comparative utcomes of neoadjuvant treatment prior to total mesorectal excision and total mesorectal excision alone in selected stage II/III low and mid rectal cancer - Kulu, Yakup; Tarantino, Ignazio; Billeter, Adrian; Diener, Markus K.; Schmidt, Thomas; Büchler, Markus W.; Ulrich, Alexis (Annals of surgical oncology, 2016)
Current guidelines advocate that all rectal cancer patients with American Joint Committee on Cancer (AJCC) stages II and III disease should be subjected to neoadjuvant therapy. However, improvements in surgical technique have resulted in single-digit local recurrence rates with surgery only.